Assessment of Cardiac Autonomic Functions by Heart Rate Recovery Indices in Patients Receiving Chest Radiotherapy - Fatihoğlu, Şefik Görkem; Kaya, Ergün Barış; Koçyiğit, Duygu; Hosrovzade, Elvin; Maharjan, Naresh; Yazıcı, Gözde; Cengiz, Mustafa; Şahiner, Mehmet Levent; Yorgun, Hikmet; Ateş, Ahmet Hakan; Aytemir, Kudret (European Journal of Therapeutics, 2022)
Objective: Although the introduction of radiation therapy for the management of thoracic malignancies has led to a significant improvement in disease-specific survival, this has resulted in the emergence of a new spectrum of cardiovascular disorders induced by radiation injury. Heart rate recovery, as a predictor of cardiovascular events and an indicator of autonomic functions, is measured non-invasively and easily. In the present study, we investigated the effects of mediastinal radiotherapy on heart rate recovery parameters. Methods: Twenty-one patients were included in this study who were planned to receive chest radiotherapy because of lymphoma or lung cancer. Heart rate recovery parameters were evaluated by treadmill exercise before and after radiotherapy. Results: We have found decrease in heart rate recovery parameters (26.05 ± 12.54 vs. 19.52 ± 12.28 for HRR1, 39.1 ± 16.15 vs. 32.86 ± 14.83 for HRR2, 42.81 ± 17.66 vs. 38.05 ± 16.14 for HRR3). The higher doses of mediastinal radiotherapy caused significant changes on heart rate recovery parameters. HRR1 changed from 25.70 ± 15.12 to 22.00 ± 14.38 in low dose group and from 26.36 ± 10.41 to 17.27 ± 10.10 in high-dose group (P < .05). Attenuation of HRR2 and HRR3 were also more evident in high mediastinal dose group (P < .05). Conclusion: Heart rate recovery parameters were decreased especially in patients who were exposed to more intense mediastinal radiation.